Elderly Tourism Behavior: A Case Study in Khon Kaen Municipality - กระจ่างพัฒน์วงษ์ หนึ่งหฤทัยรัตน์; พัวรัตนอรุณกร อรอนงค์ (KKBS Journal of Business Administration and Accountancy, 2019)
This research aimed to study tourism behavior and analyze factors influencing tourism expenditure of elders living in Khon Kaen Municipality. The sample group consisted of elders living in urban areas of Northeast Thailand. The results showed that the sample group of elders who had traveled in the last year had an average age of 65 years and average income of THB 20,968 per month. Travel expenditure averaged THB 10,208 and the study’s participants had taken an average of 2 trips. Most of the elders expressed liking to travel to historical attractions and usually traveled in the winter, findings that differed from previous studies. Multiple regression analysis using OLS showed that number of trips, length of stay for each trip, and transportation mode used for tourism were statistically significant factors influencing tourism expenditure of elders. Age, gender, and income were insignificant factors, a finding inconsistent with previous studies, which have identified correlations between gender, age, income, and tourism expenditure (Jang and Ham, 2009; Kuo and Lu, 2013; Nimhiranwong, 2001). The difference in findings may be due to the socio-economic differences between the elderly samples. This suggests that strategic planning in tourism targeting elderly populations should focus on niche marketing in order to meet the needs of different groups of elders. This information is useful for policy makers and operators working in the tourism industry.